Implementasi Good Governance dalam Perspektif Lembaga Negara Mahkamah Konstitusi - Hadji, Kuswan; Azzahra, Aisyah; Zain, Cheren Azizah; Wulandari, Saiva; Arifah, Yunita Nurul; Nurhidayati, Diah Ayu Wahyu (Judge : Jurnal Hukum, 2025)
Good Governance is defined as the management of government that is efficient, effective, and accountable, involving public participation, transparency, and accountability. The Constitutional Court, as a judicial institution, has a strategic role in overseeing the implementation of laws and resolving constitutional disputes. This research uses a qualitative method with a case study approach, analyzing the challenges faced by the Constitutional Court in implementing good governance principles and their impact on political stability in Indonesia. Although the Constitutional Court (MK) has made efforts to implement these principles, challenges such as a lack of transparency and resistance from related parties still hinder the effectiveness of oversight. Additionally, the Constitutional Court's decision in the 2024 presidential election dispute triggered massive demonstrations reflecting public dissatisfaction. This research recommends the need for increased transparency, accountability, and public participation in the legal process to strengthen public trust in institutions and maintain democratic stability in Indonesia.